2014
DOI: 10.1002/cncr.29200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary and secondary breast cancers in adolescents and young adults

Abstract: BACKGROUND: Breast cancer is one of the most common cancers in adolescent and young adult (AYA) patients (ages 15-39) and may develop de novo or in patients previously treated for cancer. This study compares the demographic, tumor, treatment characteristics, and overall survival (OS) of primary versus secondary (SMN) breast cancer in female AYAs. METHODS: All cases of invasive female AYA breast cancer in the 1998-2010 American College of Surgeons National Cancer Database were divided into 2 cohorts according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 26 publications
3
30
0
3
Order By: Relevance
“…No differences between the two groups were observed with regard to stage and grade distribution, in accordance with two small studies among HL survivors [13,29]. In contrast to our findings, two large registry-based studies in AYA cancer survivors did report that AYA cancer/HL survivors with breast SMNs were significantly more likely to have estrogen-and progestogennegative breast cancer compared to breast-FMN patients [16,17]. The percentage of triple negative breast cancer in our study was lower than that reported in a retrospective case series of breast cancer patients with a past history of chest radiotherapy (7.7% vs. 29.2%) [30].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…No differences between the two groups were observed with regard to stage and grade distribution, in accordance with two small studies among HL survivors [13,29]. In contrast to our findings, two large registry-based studies in AYA cancer survivors did report that AYA cancer/HL survivors with breast SMNs were significantly more likely to have estrogen-and progestogennegative breast cancer compared to breast-FMN patients [16,17]. The percentage of triple negative breast cancer in our study was lower than that reported in a retrospective case series of breast cancer patients with a past history of chest radiotherapy (7.7% vs. 29.2%) [30].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have addressed differences in prognostic, clinical, and/or histopathological characteristics of specific types of solid SMNs after childhood, adolescent, and young adult cancers and comparable first malignant neoplasms (FMNs) in the general population [10][11][12][13][14][15][16][17][18][19]. Since the majority of these type of studies focused on breast-SMN, most were conducted in Hodgkin lymphoma or other adolescent and young adult (AYA) cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of publications have compared survival with PMs and SPMs of the same type in AYAs . All showed an increased risk of death if a tumor occurred as an SPM versus a primary cancer, although few evaluated whether death was due to the PM or SPM.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of publications have compared survival with PMs and SPMs of the same type in AYAs. [31][32][33][34] All showed an increased risk of death if a tumor occurred as an SPM versus a primary cancer, although few evaluated whether death was due to the PM or SPM. A few studies of older adult populations of either prostate or renal cell carcinoma survivors compared survival for patients who did and did not develop an SPM.…”
Section: Discussionmentioning
confidence: 99%